178k views
4 votes
-6h + 2(4h + 3) = 1

Please provide your best explanations, as well as showing the step you took and the finished equation.

Solve for h.
Thank you!

2 Answers

4 votes

Answer:

h = -2.5

Explanation:

  1. Apply the distributed property: -6h + 8h + 6 = 1
  2. Combine like terms: 2h + 6 = 1
  3. Subtract 6 from each side, so it now looks like this: 2h = -5
  4. Divide each side by 2 to cancel out the 2 next to h. It should now look like this: h = -2.5

I hope this helps!

User Adam Jagosz
by
4.9k points
7 votes

Answer:

h = -2.5

Explanation:

-6h + 2(4h + 3) = 1

-6h + 2*4h + 2*3 = 1

-6h + 8h + 6 = 1 {combine like terms}

2h + 6 = 1

2h = 1 - 6

2h = -5

h = -5/2

h = -2.5

User Karansys
by
5.0k points